The relationship between knowledge and self-efficacy of nurses regarding early initiation of cardiopulmonary resuscitation and automated defibrillation in Saudi Arabia - Alaryani, Zainah D; Alhofaian, Aisha; Elhady, Mona (Belitung Nursing Journal, 2021)
Background: Cardiopulmonary resuscitation (CPR) and early defibrillation are the most common procedures performed by nurses as the first responders to cardiac arrest patients in the hospital setting. Therefore, nurses are demanded to have high skills for effective performance. Self-efficacy and knowledge are considered significant factors affecting early initiation of CPR and automated defibrillation. However, previous studies mostly focused on nursing students instead of frontline nurses. Objective: This research aimed to assess the relationship between nurses’ knowledge and self-efficacy regarding the early initiation of CPR and automated defibrillation of cardiac arrest patients. Methods: The study employed a cross-sectional, descriptive, correlational survey. Using convenience sampling, two hundred eighty-seven nurses working in critical areas and inpatient and outpatient departments, King Abdulaziz University Hospital (KAUH), Saudi Arabia, were selected. Resuscitation Knowledge and Self-Efficacy Scales were used for data collection (using Google Form) from November 2020 to January 2021. Descriptive statistics and Pearson correlation were used for data analysis. Results: Overall, 61.3% of participants had moderate knowledge (13.659 ± 2.175), and 63.8% had high self-efficacy (44.627 ± 58.397). The highest domain of self-efficacy was responding and rescuing, while the lowest domain was debriefing and recording. There was a significant positive relationship between knowledge and self-efficacy (p <0.001; r = 0.207). Conclusion: The positive relationship explained a high level of self-efficacy if there was a high level of knowledge. Thus, it is recommended that nursing programs apply CPR and automated defibrillation curricula during nurses’ internships, clear policies and procedures about CPR and automated defibrillation, continual updates about CPR and automated defibrillation, and knowledge and continuance training (on-job-training) about CPR and automated defibrillation, which can enhance and improve knowledge and self-efficacy among health care workers, especially for nurses.